Effects of hydrogen peroxide on membrane fluidity and Ca(2+)-transporting ATPase activity of rabbit myocardial sarcoplasmic reticulum. - Su Zhi; Yan Xiang-Dong; Li Yuan-Jian; Chen Xiu (Acta Pharmacologica Sinica, 2016)
This study was to investigate the effects of hydrogen peroxide on membrane fluidity and Ca(2+)-ATPase activity of rabbit myocardial sarcoplasmic reticulum (SR). The membrane fluidity of SR was monitored by measuring the changes in the steady state fluorescence anisotropies (rs) using diphenylhexatriene as a probe. The Ca(2+)-ATPase activity was determined by assaying the amount of inorganic phosphate (Pi) released from ATP. It was found that the membrane fluidity (rs: 0.154 +/- 0.014 vs 0.113 +/- 0.010, P < 0.01) and Ca(2+)-ATPase activity (3.1 +/- 1.3 vs 25.3 +/- 2.4 mumol Pi.h-1/mg protein, P < 0.01) were reduced in SR exposed to H2O2 (2 mmol.L-1) for 40 min. Catalase 20 micrograms.ml-1 completely prevented the SR damages caused by H2O2. H2O2 jeopardized the SR in a concentration- and time-dependent manner as measured by changes in rs values and Ca(2+)-ATPase activities, which were negatively correlated (r = 0.981, P < 0.01). These results suggest that H2O2 produces dysfunctions of the rabbit myocardial SR, and that the alteration of membrane fluidity may be one of the mechanisms responsible for the decrease of Ca(2+)-ATPase activity.